A Computational Grammar for Deep Linguistic Processing of Portuguese: LXGram, version A.4.1 - Branco, António Horta (2009)
This document presents the implementation of LXGram, in its version A.4.1. LXGram is a grammar for the computational processing of Portuguese being developed at the University of Lisbon. The present document has TR-2008-16 as its companion document, which provides a methodological introduction to the computational grammar presented here. Though they can be used independently of each other, these two documents should be seen as two parts of the same text. The present document was written in English so that the results reported in it may be used by the widest research community. The document TR-2008-16, in turn, was written in Portuguese in order for its content to be made available, for the firrst time, for an audience of speakers of Portuguese --- as other texts in English exist with approximate goals or coverage